TINJAUAN DALIL ‘URF TERHADAP MITOS LARANGAN PERKAWINAN ANTAR DUKUH (Studi Kasus di Dukuh Banyu Urip dan Dukuh Batokan Kab. Tulungagung) - Binti Maratus Solichah; Khoirul Asyfiyak; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
The writing of this research is based on the background of Javanese traditional traditions in terms of the prohibition of inter-hamlet marriages that occur in the Banyu Urip hamlet and the Batokan hamlet of Tulungagung Regency. Local people believe that if you violate it, you will get misfortune or disaster that will hit your family. This prohibition tradition is not listed in the Qur'an or Hadith. The focus of the research problem focuses on how to respond, the process of socializing the inheritance of myths and a review of Islamic law. In this case, the researcher used purposive sampling technique to collect informants, in-depth interview data collection techniques and documentation, then checked using condensation, presentation, analysis and verification techniques. The results of the study indicate that the tradition of prohibiting inter-marriage including superstition with 3 perspectives there are those who believe and obey, doubt but obey and do not believe in the existence and rules of tradition. Furthermore, socialization is formed through the process of externalization, objectivation and internalization. Finally, in terms of the argument of 'urf, the tradition is classified as 'urf sahih because it has fulfilled the conditions that make 'urf still enforced.